Стенд для испытаний гидроперфораторов - Глущенко, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The brief description is presented of the large test rig designed for study and construction
parameters determination of hydraulic perforators. The basic units of the rig were developed by
specialists if DONUGI Donetsk then transferred to FED Enterprise Kharkov where its assembly
and operational development was executed.